Analysis of the possibility of applying a condition-based maintenance model on an example of tank weapons - Igor J. Epler (Vojnotehnički Glasnik, 2013)
For any modern army it is very important to continuously maintain a high degree of operational (combat) readiness (availability) in order to maximize the effectiveness of the use of technical systems. Since determination and prediction of technical states and failures of technical systems in engineering, especially in armament, are difficult due to the impossibility of continuous condition monitoring with appropriate measuring equipment there is a need for a maintenance model that would be most helpful in taking timely action maintenance. In this paper, the subject of research is a model of maintenance of the M-84 tank  weapoons systems.   IntroductionThe M-84 tank is one of the most promising technical systems in the Serbian Army. Its use and modifications are foreseen in the next ten years. The  M-84 is characterized by good tactical and technical characteristics. It has a powerful 125 mm cannon, coupled 7.62 mm machine gun and 12.7 mm anti-aircraft machine gun. The M-84 tank has an automatic battery charger and a fire control system. The fire control system enables fast target tracking and stabilization of the cannon barrel, which is a prerequisite for timely and favorable effect on the target. There are certain ambiguities in the existing model of maintenance of tank weapons.   Technical diagnostics Technical diagnostics, as a part of the process of condition-based maintenance, should determine technical conditions of components or technical systems with certain accuracy at a point in time.   Maintenance strategy A maintenance strategy can be defined as a variant of a maintenance system determined by a concept, organization and character of maintenance procedures, as well as the relationship between the various levels at which maintenance is performed. It is defined for technical system parts, individual technical systems and for system maintenance as a whole. The basic maintenance strategies implemented today are: -      corrective maintenance, -      preventive maintenance, -      combined maintenance.   Some developed condition-based maintenance models Condition-based maintenance models can be classified in two groups as: -      models of technical change in the current situation (with a use of condition inspection), -      models of technical change in the situation (with a use of condition diagnostics).   Some developed condition-based maintenance models The  models of condition-based maintenance  include: -      condition-based maintenance model with parameters control, -      condition-based maintenance model with the control of reliability levels.   Condition-based maintenance model with parameters control Condition-based maintenance model with parameters control can be with: -      periodic diagnostic controls (“the constant date”), -      economic setting of the intervals of diagnostic controls, -      continous diagnostic controls.   Condition-based maintenance model with the reliability level control The essence of the condition-based maintenance model with the control of reliability levels is to use resources between two repairs without limitation, with execution of maintenance activities necessary to fix the failure occurred, while the actual reliability level is within the boundaries of the set (permissible) norms. If deviations from these norms occur,  the causes of deviations are analysed and measures taken to increase the reliability level of individual components and the system.   The possibilities of the application of the condition-based maintenance model on the example of tank weapons The application of the condition-based maintenance model with parameters control is hard to realize in tank weapons, except for a tank cannon barrel. In this case,  the intensity of the stress in the material on the critical barrel sections can be measured during operation, using electrical extensiometers. Voltage intensity can be used to determine the safety degree on the observed sections. Comparing the actual level of safety with the projected level, we can decide on the action of maintenance to be implemented in order to prevent failure. The data from Table 1 and the methodology for the selection of maintenance strategies (Figure 1), in the case of a weakened or damaged magnets for electric firing on the tank 7.62 mm machine gun indicate the possibilities of the condition-based maintenance model with the control of reliability levels. Conclusion The introduction of the condition-based maintenance model would minimize overall costs because the “reliability reserve” of components or representative tank weapons would be used to the maximum. On the other hand, the current maintenance system of tank weapons would experience some changes. The intensity of preventive maintenance actions could be reduced and particular maintenance levels might be omitted  as well as specific types of maintenance (easy maintenance, medium maintenance).